A study on disinfection process in dialysis unit of multispecialty hospital - DR. MEENAL KULKARNI,; BRIG.(DR). ANIL PANDIT. MD,; DR. PRAFUL DESAI. BDS. MBA (HHM), (International Journal of Pharma and Bio Sciences, 2017)
The number of patients on maintenance haemodialysis is increasing. Chronic haemodialysis patients have an increased infection risk. HD facility is very conducive for transmission of infection. A study to understand the present disinfection process in the dialysis unit of a hospital was carried out with the help of check list. The study shows that disinfection at the site of HD catheter is not appropriate. In case of AV- fistula the patient was not made aware to wash hands before the prick at the site, also there is a gross negligence towards the handing of sterile equipment’s, and non-use of PPE. The touch surface disinfection was also lacking. In case of disinfectant levels of machine, expired disinfectant solutions were found. The study concluded that the disinfection process had certain shortfalls. Attention is needed towards the process and frequency of surface disinfection, reprocessing techniques and formulation and strict implementation of standard operating procedures.